Prophylactic intracameral vancomycin: efficacy in preventing endophthalmitis after cataract surgery - Goswami, Manash Kumar; Hossain, Md. Ferdous; Asaduzzaman, Md (IMC Journal of Medical Science, 2017)
Background and objective: Post Operative endophthalmitis is rare but devastating complication in ocular surgery. The present study determined the efficacy of intracameral vancomycin after phaco-emusification cataract surgery to prevent endophthalmitis. Method: A total of 768 cases who had undergone phaco-emusification cataract surgery were included in the study. Every alternate patient received 0.5 ml injection of vancomycin (1mg in 0.1 ml) in the anterior chamber after completion of phaco-emulcification and formation of anterior chamber. All the patients were examined for symptoms and signs of bacterial endophthalmitis at 24 hrs, 7 days, 15 days and subsequently at 1, 3 and 6 months following surgery. Results: No endophthalmitis case was recorded at any time period during 6 month follow up in either group. However, significantly higher number of cases in vancomycin group had cells in anterior chamber and disturbances in visual acuity at day 15 following surgery. Conclusion: Vancomycin did not have any prophylactic role in preventing endophthalmitis. Proper aseptic measures are important to prevent any infection in ocular surgery. IMC J Med Sci 2016; 10(1): 24-28